Born Weak, Growing Strong: Anti‐Government Protests as a Signal of Rebel Strength in the Context of Civil Wars. Issue 3 (6th April 2018) - Leventoğlu, Bahar; Metternich, Nils W.
Abstract: All rebel organizations start weak, but how do they grow and achieve favorable conflict outcomes? We present a theoretical model that allows for rebel organizations to gain support beyond their "core" and build their bargaining power during fighting. We highlight that rebel organizations need to win over crucial parts of society to generate the necessary support that allows them to attain favorable civil conflict outcomes. We find empirical support for the argument that low‐income individuals who initially fight the government (rebel organizations) have to convince middle‐class individuals to turn out against the government to gain government concessions. Empirically, we demonstrate that government concessions in the form of peace agreements and the onset of negotiations become more likely when protest occurs in the context of civil conflicts. Replication Materials: The data, code, and any additional materials required to replicate all analyses in this article are available on the American Journal of Political Science Dataverse within the Harvard Dataverse Network, at:http://doi.org/10.7910/DVN/MYDZNF .